2016
DOI: 10.15171/jlms.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Intravenous and Percutaneous Low Level Laser Therapy in the Management of Shoulder Myofascial Pain Syndrome

Abstract: Introduction: Myofascial pain syndrome (MPS) treatment is challenging with a high recurrence rate and still lacks a clear treatment frame. Therefore research on new, more efficient and long lasting effect treatment modalities is necessary. This study looked at the effects of intravenous laser therapy (IVL) and percutaneous low level laser (PLLL) in the management of shoulder MPS. Methods: In this randomized controlled trial, 30 patients fulfilling inclusion criteria were randomly equally allocated to 3 groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[15][16][17][18][19][20] Imani et al and Munguia et al concluded that almost 60% of the literature between 2000 to 2018 demonstrated that LLLT was useful in reducing pain and trigger point sensitivity, improving the quality of life. 21,22 Momenzadeh et al 23 reached the same result. 24 Several mechanisms of action have been proposed for pain reduction by LLLT.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…[15][16][17][18][19][20] Imani et al and Munguia et al concluded that almost 60% of the literature between 2000 to 2018 demonstrated that LLLT was useful in reducing pain and trigger point sensitivity, improving the quality of life. 21,22 Momenzadeh et al 23 reached the same result. 24 Several mechanisms of action have been proposed for pain reduction by LLLT.…”
Section: Introductionmentioning
confidence: 66%
“…The superior results of LLLT in reducing pain, in accordance with our VAS scores, agree with many reports that investigated the effect of laser light on reducing pain. 23,34,35 Uemoto et al 36 investigated the effect of laser therapy and needling on deactivating MTrPs. In this research, in 4 sessions of laser irradiation at wavelength=795 nm at power=80 mW and an exposure rate of 4 J/cm 2 , a significant pain reduction compared to a control group was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, if patients were to be given an increased dose of an analgesic drug, it may mask the effect of ILIB pain control, causing participants to be excluded. In addition, although there has been no report about obvious adverse events of ILIB treatment so far, patients with recent hemorrhage history, photosensitivity, infection status, or pregnancy were excluded to receive ILIB treatment, according to our routine clinical practice [ 6 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it is also difficult to predict the muscular area involved in the case of a preventive application of PBM. Thus, another type of PBM is the intravascular laser irradiation of blood (ILIB), which was developed more than 30 years age for the treatment of systemic diseases [28][29][30][31]. A modification of this technique to a transcutaneous, noninvasive application modality is denominated noninvasive laser irradiation of blood (NLIB), systemic photobiomodulation (SPBM) [31], or vascular photobiomodulation (VPBM) [32].…”
Section: Introductionmentioning
confidence: 99%